2005
DOI: 10.4992/jjpsy.76.244
|View full text |Cite
|
Sign up to set email alerts
|

The effects of repetition and dual-task on the output monitoring errors

Abstract: We investigated output-monitoring errors in a modified source-monitoring paradigm. Unlike the traditional paradigm that involves two phases, learning and monitoring, the modified paradigm involves three phases, learning, enactment, and monitoring. Three experiments produced two major findings. First, compared with the traditional paradigm, the modified paradigm produced fewer monitoring errors. Second, performing a dual-task during the enactment phase increased monitoring errors for the items that participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In this case, output monitoring error occurred when a participant judged an action phrase as "recollected," even though the participant failed to perform the action during the recall test phase. Experiment 1A replicated a test conducted by Sugimori et al (2005), in which attention levels (full vs. divided) were manipulated in the recall test phase to confirm that output monitoring error required both repeated enactment during the learning phase and a divided attention task (counting numerals) during the recall test phase. Experiment 1B manipulated the time interval (immediate vs. 7-day delay) between the recall test and output monitoring test phases to confirm that delayed monitoring also reduces the ability to consciously recollect.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…In this case, output monitoring error occurred when a participant judged an action phrase as "recollected," even though the participant failed to perform the action during the recall test phase. Experiment 1A replicated a test conducted by Sugimori et al (2005), in which attention levels (full vs. divided) were manipulated in the recall test phase to confirm that output monitoring error required both repeated enactment during the learning phase and a divided attention task (counting numerals) during the recall test phase. Experiment 1B manipulated the time interval (immediate vs. 7-day delay) between the recall test and output monitoring test phases to confirm that delayed monitoring also reduces the ability to consciously recollect.…”
mentioning
confidence: 84%
“…Applying these findings to the new paradigm of output monitoring, Sugimori et al (2005) found that participants who had performed a divided attention task were unable to recollect having performed the action phrase during the recall test phase. If the findings from the "famous" task are applied to the new paradigm, output monitoring error should also occur if the output monitoring test phase is conducted 7 days after the recall test phase.…”
mentioning
confidence: 99%
See 2 more Smart Citations